Programmable mutually exclusive alternative splicing for generating RNA and protein diversity - Melina Mathur (Nature Portfolio, 2019)
Alternative splicing expands the genetic coding capacity and proteomic diversity of the cell. Here the authors create a synthetic biology platform for regulating four programmable exons in modular transcription factors.